EFFECTIVE PAI LEARNING STRATEGIES IN DEVELOPING RELIGIOUS AWARENESS IN STUDENTS - Sri Wulan Ayu Lestari Damanik; Koko Khoerudin (CV. Lafadz Jaya, 2026)
Islamic Religious Education (PAI) in Indonesia plays a central role in shaping student character. Therefore, learning strategies are considered the initial step that determines success in learning, particularly in increasing students' religious awareness. Furthermore, PAI learning strategies must reflect inherent Islamic values and produce Islamic behavior. Consequently, it is important to provide instruction with appropriate strategies so that students can apply them in society as a concrete form of their religious awareness. The purpose of this study is to discuss and determine PAI learning strategies considered effective in increasing religious awareness among students at PPS TQ TU Arroyyan Ujung Batu. This study uses a descriptive qualitative method, and the results show that the religious awareness of the students at PPS TQ TU Arroyyan Ujung Batu varies for each child, but overall it is relatively similar, with a fairly good level of religious awareness. Approximately 75% of students have good religious awareness, while the remaining 25% have sufficient religious awareness. The majority of students already possess religious awareness, while a small minority do not yet have sufficiently good religious awareness.